Comparative Study of Fatigue Damage Models Using Different Number of Classes Combined with the Rainflow Method - Zengah, S.; Aid, A.; Benguediab, M. (Engineering, Technology & Applied Science Research, 2013)
Fatigue damage increases with applied load cycles in a cumulative manner. Fatigue damage models play a key role in life prediction of components and structures subjected to random loading. The aim of this paper is the examination of the performance of the “Damaged Stress Model”, proposed and validated, against other fatigue models under random loading before and after reconstruction of the load histories. To achieve this objective, some linear and nonlinear models proposed for fatigue life estimation and a batch of specimens made of 6082T6 aluminum alloy is subjected to random loading. The damage was cumulated by Miner’s rule, Damaged Stress Model (DSM), Henry model and Unified Theory (UT) and random cycles were counted with a rain-flow algorithm. Experimental data on high-cycle fatigue by complex loading histories with different mean and amplitude stress values are analyzed for life calculation and model predictions are compared.